University faculty research training and performance: a case from Peru - Simbron-Espejo, Shirley (2020)
The present study aims to understand faculty research training in private universities in Lima, Peru. The paradigm that guided the study was interpretive, under the reflexive critical approach based on introspection of the experience. The methodology was qualitative, based on the thesis and its contradiction, the antithesis, the synthesis, from Hegel's perspective. The social actors were represented by faculty from Peruvian universities with different selection criteria; sixteen professors were selected as key informants. Data were collected through assertive communication strategies, using participant observation, focus groups, and interviews as techniques. In addition, the study used different research instruments to gather information such as descriptive record sheets, reflection scripts, questionnaires, video recording being key always, as a resource. Data analysis was performed with Atlas TI software using both content analysis and grounded theory. According to the observed dimensions, research has not been promoted as a core element. There is a predominance of doing research from a positivist paradigm, and universities have updated their policies to promote research dissemination with predominance on indexed article publication. The results reveal that there were transcendental changes in research training from the multidimensionality of knowledge. Hence, private universities must promote research training as the backbone of the research work focused on its strategic research plans, where the entire university community can investigate multiple social realities from different epistemic perspectives.